2022
DOI: 10.1002/adfm.202211774
|View full text |Cite
|
Sign up to set email alerts
|

Restraining Shuttle Effect in Rechargeable Batteries by Multifunctional Zeolite Coated Separator

Abstract: The detrimental shuttle of soluble species from cathode to anode inside battery, is a critical thorn limiting stability and reversibility of rechargeable battery. Herein, an ordered pore-window of zeolite molecular sieve is employed to effectively block shuttle of soluble matters, and prepared zeolite powder into thin zeolite layer (5 µm thick) coated on celgard separator (zeolite@celgard) with flexible and grid-scale fabrication features. External pressure is applied to press zeolite@celgard to reduce existed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Relying on the size effect and particular influence on the solvation structure, porous materials such as metal–organic frameworks (MOFs) and zeolite molecular sieves (ZMS) , have been used to regulate the properties of electrolytes and exhibit unusual performances. Recently, a 3 Å ZMS film is introduced to transform the one-step desolvation process to the step-by-step desolvation process (Figure b) .…”
Section: Hard Carbon Anodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Relying on the size effect and particular influence on the solvation structure, porous materials such as metal–organic frameworks (MOFs) and zeolite molecular sieves (ZMS) , have been used to regulate the properties of electrolytes and exhibit unusual performances. Recently, a 3 Å ZMS film is introduced to transform the one-step desolvation process to the step-by-step desolvation process (Figure b) .…”
Section: Hard Carbon Anodesmentioning
confidence: 99%
“…3 Å ZMS film has been added into the assembly of Na metal batteries (SMBs) and placed between the Na metal and the separator manufacturing sieved electrolytes . Relying on the size effect, the cation-dominated SSIP is blocked and CIP/AGG is successfully retained in the nanopore due to size effect, which is considered to be similar to superconcentrated electrolytes. , The significantly reduced electrolyte activity effectively suppresses the violent decomposition of metallic Na and the release of combustible gases (Figure d). In addition, a robust SEI with abundant NaF and Na 2 O was identified, which has been shown to be beneficial for reversible Na plating and stripping.…”
Section: Na Metal Anodesmentioning
confidence: 99%
“…Reproduced with permission. 100 Copyright 2022, Wiley. (e) Schematic illustration of the working mechanism and the cross-sectional SEM image of the zeolite@Celgard separator.…”
Section: Multifunctional Acid/h 2 O Scavenging Separatorsmentioning
confidence: 99%
“…Reproduced with permission. 100 Copyright 2022, Wiley. (f) The contact angle of Celgard and zeolite separator towards electrolyte, and digital pictures of zeolite@Celgard with large-scale preparation and flexibility features.…”
Section: Multifunctional Acid/h 2 O Scavenging Separatorsmentioning
confidence: 99%
“…Quasi-solid-state Al–S batteries employing cathode hosts with Co–N 4 as the catalytic sites facilitating Al–Cl and S–S bonds breakage exhibit effectively alleviated polarization, and the use of the quasi-solid electrolyte inhibiting the shuttle effect also improves the cyclic stability . Furthermore, engineering of separator interface has been demonstrated to be an effective approach in mitigating the shuttle effect in metal–S batteries, as the modification layer of separators can weaken the transport of polysulfides across the separator via physicochemical adsorption . Previous researches have reported that carbonaceous nanomaterials with a high surface area and suitable pore size as the modification layer of separator can effectively enhance cyclic stability of the Al–S batteries by anchoring polysulfides during battery reaction. , When combined with nitrogen-based functional groups or transition-metal-based catalysts, the electrochemical reaction of the adsorbed polysulfide can be promoted, which leads to reduced polarization .…”
Section: Introductionmentioning
confidence: 99%